Modified cellulose-polyethyleneimine grafted copolymer reinforcing agent, preparation method and recycling process of degradable corrugated paper
Through the modified cellulose-polyethyleneimine graft copolymer reinforcement and the improved corrugated paper recycling and treatment process, the problem of incomplete removal of impurities during corrugated paper recycling is solved, and the mechanical and environmental performance of the paper is significantly improved, and the effective recycling of resources and environmentally friendly production is achieved.
Patent Information
- Application Number
- CN202510406574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
AI Technical Summary
In the existing corrugated paper recycling and treatment process, impurities cannot be effectively removed during the crushing and cooking of waste corrugated paper, resulting in low quality of recycled pulp. Incomplete de-inking and damaged fibers often occur during the recycling process, which affects the strength and performance of recycled paper.
The modified cellulose-polyethyleneimine graft copolymer enhancer is used to significantly improve the mechanical and environmental performance of the paper by graft copolymerization reaction.
It significantly improves the mechanical properties, water resistance and surface properties of corrugated paper, extends the service life of paper, reduces the damage rate, and realizes effective recycling of resources and environmentally friendly production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, and in particular to a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, a preparation method and a recycling process for degradable corrugated paper. Background Art
[0002] Corrugated paper is a board-shaped material made by gluing noodle paper and corrugated paper formed by corrugating rollers. It is generally divided into two categories: single corrugated paperboard and double corrugated paperboard. According to the size of the corrugation, it is divided into five types: A, B, C, E, and F. The invention and application of corrugated paper has a history of more than 100 years. It has the advantages of low cost, light weight, easy processing, high strength, excellent printing adaptability, and convenient storage and transportation. More than 80% of corrugated paper can be recycled. Corrugated paper can be used as packaging for food or digital products. It is relatively environmentally friendly and widely used.
[0003] Although corrugated paper has many advantages, there are still some problems in the actual production and application process: (1) Low recycling efficiency: In the current recycling process, impurities are often not effectively removed during the crushing and cooking of waste corrugated paper, resulting in low quality of recycled pulp. Problems such as incomplete deinking and fiber damage often occur during the recycling process, affecting the strength and performance of recycled paper. (2) Inadequate mechanical properties: Existing corrugated paper products perform poorly in terms of ring crush index, bursting index, tensile index and smoothness, especially in high-strength applications, their performance is difficult to meet the requirements, and the folding resistance and water absorption value of paper are high, resulting in easy damage in a humid environment. (3) Environmental protection requirements: Existing corrugated paper products still have room for improvement in environmental protection performance, especially for the requirement of easy degradation, which may not be fully met by existing reinforcing agents and treatment processes.
[0004] Therefore, there is an urgent need for a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, a preparation method and a recycling process for degradable corrugated paper to solve the problems of poor reinforcing agent effect and unstable paper performance in the prior art, and significantly improve the mechanical properties, water resistance and surface properties of corrugated paper, thereby achieving effective recycling of resources and environmentally friendly production. Summary of the invention
[0005] To this end, the present invention provides a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, a preparation method and a recycling process for degradable corrugated paper, which solves the problems of poor reinforcing agent effect and unstable paper performance in the prior art.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: According to a first aspect of the present invention, there is provided a method for preparing a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, comprising the following steps: S1. adding sodium periodate to a cellulose suspension, placing it in a dark environment for reaction, after the reaction is completed, pouring the cellulose suspension into a coagulation bath for coagulation, finally separating the coagulated cellulose from the coagulation bath, and then drying it at a temperature of 50-80° C. for 5-10 hours until it is completely dried to obtain cellulose containing aldehyde groups; S2. Add 10-16 parts of ethyleneimine monomer and 3-4.5 parts of distilled water as solvent, continue to add 0.01-0.05 parts of initiator, and prepolymerize at 55-65 ° C for 1.5-3.5h to obtain prepolymerized polyethyleneimine; S3. Add the cellulose containing aldehyde groups obtained in S1 and the prepolymerized polyethyleneimine obtained in S2 into the reaction tank, then add the initiator and the catalyst, raise the temperature to 80-90°C for graft copolymerization for 3-5h, use a pH meter to monitor the pH value of the system in real time, and keep the pH value at 8.5-9.5. After the reaction is completed, separate and dry to obtain a cellulose-polyethyleneimine graft copolymer; S4. 80-120 parts of cellulose-polyethyleneimine graft copolymer, 4-8 parts of sodium citrate and 30-60 parts of phosphate buffer are mixed evenly, and the temperature is raised to 30-60°C. 30-40wt% glyoxal is added dropwise at a rate of 0.2-0.6mL / min, and the pH value is maintained at 8.5-9.5. The temperature is raised to 70-80°C and the reaction is kept warm for 3-5h. Then, the pH value is adjusted to 3-4 and the solid content is adjusted to 13-15wt% by dilution with deionized water to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
[0007] Furthermore, the preparation method of the cellulose suspension in S1 is: Adding cellulose with a mass fraction of 5-10% to an ethanol-water solution, ultrasonically treating, adding a hydrochloric acid solution with a concentration of 1-5% to react at 85-115° C., and obtaining a nanocellulose suspension after treatment; The cellulose is microcrystalline cellulose prepared by hydrolyzing waste cotton scraps with nitric acid, and the length and width of the cellulose particles are in the micron level.
[0008] Furthermore, the mass ratio of the cellulose suspension to sodium periodate is (8-12):(10-15).
[0009] Furthermore, the initiators in S2 are ammonium persulfate and sodium bisulfite, wherein the mass ratio of ammonium persulfate to sodium bisulfite is (1-2): (1-3).
[0010] Furthermore, the catalyst in S3 is Fe 3+ and CH3CH2OH, Fe 3+ The usage ratio of CH3CH2OH is (1-3):(1-2).
[0011] Furthermore, the mass ratio of the cellulose containing aldehyde groups to the prepolymerized polyethyleneimine in S3 is (6-9):(1-3).
[0012] Furthermore, the method for adjusting the pH value in S3 and S4 is: When the pH value drops: add 0.01M NaOH solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.5; When the pH value rises: add 0.01M HCl solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.5.
[0013] According to a second aspect of the present invention, there is provided a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, which is prepared by the above-mentioned preparation method.
[0014] According to a third aspect of the present invention, a process for recycling degradable corrugated paper is provided, wherein the modified cellulose-polyethyleneimine graft copolymer reinforcing agent prepared by the above-mentioned preparation method comprises the following steps: (1) The waste corrugated paper is crushed, and then a deinking agent with a content of 6-9 kg / T and water with a mass ratio of 1:3 to the waste corrugated paper are added, and the mixture is stirred and heated to 80-90°C for steaming. After the mixture is evenly mixed, waste paper pulp is obtained, and then the waste paper pulp is washed, screened, concentrated, and impurities removed to obtain paper pulp; (2) Add modified cellulose-polyethyleneimine graft copolymer reinforcing agent to the pulp, mix evenly, raise the temperature to 100°C, and keep it warm for 20-30 minutes; (3) stirring a silicate dispersion having a mass fraction of 13-18% and adding it to the thickened pulp, mixing the mixture evenly and then drying and forming the mixture to obtain a corrugated paper semi-finished product; (4) Lay the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then irradiate the semi-finished corrugated paper with the sizing agent on the surface with an ultraviolet curing machine to obtain a finished product.
[0015] Furthermore, the silicate is one or more of sodium metasilicate, sodium silicate, potassium silicate and calcium silicate.
[0016] The present invention has the following advantages: 1. The modified cellulose-polyethyleneimine graft copolymer reinforcing agent used in this application can improve the processing performance of pulp and improve the flatness and smoothness of paper by increasing crosslinking through grafting. During the production process, the reinforcing agent makes the combination between pulp fibers more firm, reduces the loss of pulp during processing, and improves processing efficiency. In addition, the reinforcing agent can also improve the printing adaptability of paper, so that the printing ink adheres better to the surface of the paper and the printed pattern is clearer.
[0017] 2. The recycling process in this application can significantly improve the mechanical properties of pulp, so that the final recycled corrugated paper has higher strength and durability, especially the tensile strength, tear strength and burst resistance of the paper are greatly improved, thereby extending the service life of the paper and reducing the breakage rate.
[0018] 3. The preparation process of the present application can significantly improve the performance of paper, reduce the amount of raw materials used, and thus reduce production costs. In addition, by improving the quality and performance of paper, the competitiveness of products in the market is enhanced, bringing higher economic benefits to enterprises, with the dual advantages of environmental protection and economy, and providing reliable technical support for the recycling, production and application of degradable corrugated paper. DETAILED DESCRIPTION
[0019] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention provides a method for preparing a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, comprising the following steps: S1. adding sodium periodate to a cellulose suspension, placing it in a dark environment for reaction, after the reaction is completed, pouring the cellulose suspension into a coagulation bath for coagulation, finally separating the coagulated cellulose from the coagulation bath, and then drying it at a temperature of 50-80° C. for 5-10 hours until it is completely dried to obtain cellulose containing aldehyde groups; S2. Add 10-16 parts of ethyleneimine monomer and 3-4.5 parts of distilled water as solvent, continue to add 0.01-0.05 parts of initiator, and prepolymerize at 55-65 ° C for 1.5-3.5h to obtain prepolymerized polyethyleneimine; Wherein, the molecular weight of the prepolymerized polyethyleneimine is less than 500,000; S3. Add the cellulose containing aldehyde groups obtained in S1 and the prepolymerized polyethyleneimine obtained in S2 into the reaction tank, then add the initiator and the catalyst, raise the temperature to 80-90°C for graft copolymerization for 3-5h, use a pH meter to monitor the pH value of the system in real time, and keep the pH value at 8.5-9.5. After the reaction is completed, separate and dry to obtain a cellulose-polyethyleneimine graft copolymer; S4. 80-120 parts of cellulose-polyethyleneimine graft copolymer, 4-8 parts of sodium citrate and 30-60 parts of phosphate buffer are mixed evenly, and the temperature is raised to 30-60°C. 30-40wt% glyoxal is added dropwise at a rate of 0.2-0.6mL / min, and the pH value is maintained at 8.5-9.5. The temperature is raised to 70-80°C and the reaction is kept warm for 3-5h. Then, the pH value is adjusted to 3-4 and the solid content is adjusted to 13-15wt% by dilution with deionized water to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
[0021] In S1, the preparation method of the cellulose suspension is: Cellulose with a mass fraction of 5-10% is added to an ethanol-water solution, subjected to ultrasonic treatment, and a hydrochloric acid solution with a concentration of 1-5% is added to react at 85-115° C. for 1-3 hours to obtain a nanocellulose suspension after treatment.
[0022] The ethanol-water solution is a mixture of 70% ethanol and 30% water.
[0023] The cellulose is microcrystalline cellulose prepared by hydrolyzing waste cotton scraps with nitric acid, and the length and width of the cellulose particles are in the micron level.
[0024] Specifically, the mass ratio of the cellulose suspension to sodium periodate is (8-12):(10-15).
[0025] Specifically, the initiators in S2 are ammonium persulfate and sodium bisulfite, wherein the mass ratio of ammonium persulfate to sodium bisulfite is (1-2):(1-3).
[0026] Specifically, the catalyst in S3 is Fe 3+ and CH3CH2OH, Fe 3+ The usage ratio of CH3CH2OH is (1-3):(1-2).
[0027] The mass ratio of cellulose containing aldehyde groups to prepolymerized polyethyleneimine in S3 is (6-9):(1-3).
[0028] Specifically, the method for adjusting the pH value in S3 and S4 is: When the pH value drops: add 0.01M NaOH solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.5; When the pH value rises: add 0.01M HCl solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.5.
[0029] The invention provides a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, which is prepared by the above-mentioned preparation method.
[0030] The present invention provides a recycling process for degradable corrugated paper, using the modified cellulose-polyethyleneimine graft copolymer reinforcing agent prepared by the above preparation method, comprising the following steps: (1) The waste corrugated paper is crushed, and then a deinking agent with a content of 6-9 kg / T and water with a mass ratio of 1:3 to the waste corrugated paper are added, and the mixture is stirred and heated to 80-90°C for steaming. After the mixture is evenly mixed, waste paper pulp is obtained, and then the waste paper pulp is washed, screened, concentrated, and impurities removed to obtain paper pulp; (2) Add modified cellulose-polyethyleneimine graft copolymer reinforcing agent to the pulp, mix evenly, raise the temperature to 100°C, and keep it warm for 20-30 minutes; (3) stirring a silicate dispersion having a mass fraction of 13-18% and adding it to the thickened pulp, mixing the mixture evenly and then drying and forming the mixture to obtain a corrugated paper semi-finished product; (4) Lay the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then irradiate the semi-finished corrugated paper with the sizing agent on the surface with an ultraviolet curing machine to obtain a finished product.
[0031] Specifically, the silicate is one or more of sodium metasilicate, sodium silicate, potassium silicate, and calcium silicate. Preferably, sodium metasilicate is selected in the present application.
[0032] Example 1 This embodiment provides a method for preparing a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, comprising the following steps: S1. Add 120 g of sodium periodate to 80 g of cellulose suspension, place in dark conditions to react for 6 h, after the reaction is completed, pour the cellulose suspension into 70% ethanol aqueous solution to coagulate the cellulose, finally separate the coagulated cellulose from the coagulation bath, and then dry at 60 ° C for 8 h until completely dried to obtain cellulose containing aldehyde groups; The preparation method of the cellulose suspension is as follows: adding 10% cellulose by mass into an ethanol-water solution, ultrasonically treating it, adding a 3% hydrochloric acid solution and reacting it at 100°C for 2 hours, and obtaining a nanocellulose suspension after treatment.
[0033] S2. 160 g of ethyleneimine monomer was added, followed by spraying 45 g of distilled water as a solvent, 0.3 g of ammonium persulfate and 0.2 g of sodium bisulfite were added under stirring, and prepolymerization was carried out at 55 ° C for 1.5 h, and dried to obtain a powdered pre-polyethyleneimine, the molecular weight of the pre-polymerized polyethyleneimine being less than 500,000; S3. Add 90g of cellulose containing aldehyde groups obtained in S1 and 30g of prepolymerized polyethyleneimine obtained in S2 into the reaction tank, then add 0.6g of ammonium persulfate and 0.4g of sodium bisulfite, and at the same time add 0.4g of a homemade catalyst, wherein the ratio of Fe³⁺ to CH3CH2OH in the homemade catalyst is 1:3, and heat to 90°C for graft copolymerization for 3.5h. Use a pH meter to monitor the pH value of the system in real time to maintain the pH value at 8.5-9.5. After the reaction is completed, separate and dry to obtain a cellulose-polyethyleneimine graft copolymer; S4. Mix 100g of cellulose-polyethyleneimine graft copolymer, 5g of sodium citrate and 50mL of phosphate buffer evenly, then heat to 40°C, add 40wt% glyoxal at a drop rate of 0.5mL / min, keep the pH at 8.5-9.5, heat to 80°C and react for 5h, then dilute with deionized water to adjust the pH to 3-4 and the solid content to 15wt%, to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
[0034] This embodiment provides a recycling process for degradable corrugated paper, comprising the following steps: (1) Grinding the waste corrugated paper to a particle size of less than 5 mm, then adding 7 kg / T of deinking agent and water in a mass ratio of 1:3 to the waste corrugated paper, heating to 85°C, heating and stirring for 60 minutes for steaming, mixing evenly to obtain waste paper pulp, and then washing, screening, concentrating and removing impurities from the waste paper pulp to obtain paper pulp; (2) Add 0.5% of the weight of the pulp into the modified cellulose-polyethyleneimine graft copolymer reinforcing agent, mix well, heat to 100°C, and keep warm for 20 minutes; (3) Stirring a 15% silicate dispersion into the thickened pulp, wherein the amount of the silicate dispersion added is 2% of the mass of the pulp, and after mixing evenly, drying and forming the mixture, wherein the drying temperature is controlled at 110°C and the drying time is 40 minutes, to obtain a semi-finished corrugated paper product; (4) Spread the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then dry the semi-finished corrugated paper after the surface sizing, the drying temperature is controlled at 110°C, the drying time is 60 minutes, and then stand for 24 hours to obtain the finished product.
[0035] Example 2 This embodiment provides a method for preparing a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, comprising the following steps: S1. Add 100 g of sodium periodate to 80 g of cellulose suspension, place in dark conditions to react for 6 h, after the reaction is completed, pour the cellulose suspension into 70% ethanol aqueous solution to coagulate the cellulose, finally separate the coagulated cellulose from the coagulation bath, and then dry at 60 ° C for 8 h until completely dried to obtain cellulose containing aldehyde groups; S2. 120 g of ethyleneimine monomer was added, followed by spraying 45 g of distilled water as a solvent, 0.3 g of ammonium persulfate and 0.2 g of sodium bisulfite were added under stirring, and prepolymerization was carried out at 55 ° C for 1.5 h, and dried to obtain a powdered pre-polyethyleneimine, the molecular weight of the pre-polymerized polyethyleneimine being less than 500,000; S3. Add 90g of cellulose containing aldehyde groups obtained in S1 and 30g of prepolymerized polyethyleneimine obtained in S2 to the reaction tank, then add 0.6g of ammonium persulfate and 0.4g of sodium bisulfite, and at the same time add 0.4g of homemade catalyst. 3+ The ratio of CH3CH2OH is 1:3, the temperature is raised to 90°C for graft copolymerization reaction for 3.5 hours, the pH value of the system is monitored in real time using a pH meter to maintain the pH value at 8.5-9.5, and after the reaction is completed, the cellulose-polyethyleneimine graft copolymer is separated and dried to obtain; S4. Mix 100g of cellulose-polyethyleneimine graft copolymer, 5g of sodium citrate and 50mL of phosphate buffer evenly, then heat to 40°C, add 40wt% glyoxal at a drop rate of 0.5mL / min, keep the pH at 8.5-9.5, heat to 80°C and react for 5h, then dilute with deionized water to adjust the pH to 3-4 and the solid content to 15wt%, to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
[0036] This embodiment provides a recycling process for degradable corrugated paper, comprising the following steps: (1) Grinding the waste corrugated paper to a particle size of less than 5 mm, then adding 7 kg / T of deinking agent and water in a mass ratio of 1:3 to the waste corrugated paper, heating to 85°C, heating and stirring for 60 minutes for steaming, mixing evenly to obtain waste paper pulp, and then washing, screening, concentrating and removing impurities from the waste paper pulp to obtain paper pulp; (2) Add 0.5% of the weight of the pulp into the modified cellulose-polyethyleneimine graft copolymer reinforcing agent, mix well, heat to 100°C, and keep warm for 20 minutes; (3) Stirring a 15% silicate dispersion into the thickened pulp, wherein the amount of the silicate dispersion added is 2% of the mass of the pulp, and after mixing evenly, drying and forming the mixture, wherein the drying temperature is controlled at 110°C and the drying time is 40 minutes, to obtain a semi-finished corrugated paper product; (4) Spread the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then dry the semi-finished corrugated paper after the surface sizing, the drying temperature is controlled at 110°C, the drying time is 60 minutes, and then stand for 24 hours to obtain the finished product.
[0037] Example 3 This embodiment provides a method for preparing a modified cellulose-polyethyleneimine graft copolymer reinforcing agent, comprising the following steps: S1. Add 100 g of sodium periodate to 80 g of cellulose suspension, place in dark conditions to react for 6 h, after the reaction is completed, pour the cellulose suspension into 70% ethanol aqueous solution to coagulate the cellulose, finally separate the coagulated cellulose from the coagulation bath, and then dry at 60 ° C for 8 h until completely dried to obtain cellulose containing aldehyde groups; S2. 100 g of ethyleneimine monomer was added, followed by spraying 30 g of distilled water as a solvent, 0.3 g of ammonium persulfate and 0.2 g of sodium bisulfite were added under stirring, and prepolymerized at 55 ° C for 1.5 h, and dried to obtain a powdered pre-polyethyleneimine, the molecular weight of the pre-polymerized polyethyleneimine being less than 500,000; S3. Add 90g of cellulose containing aldehyde groups obtained in S1 and 30g of prepolymerized polyethyleneimine obtained in S2 to the reaction tank, then add 0.6g of ammonium persulfate and 0.4g of sodium bisulfite, and at the same time add 0.4g of homemade catalyst. 3+ The ratio of CH3CH2OH is 1:3, the temperature is raised to 90°C for graft copolymerization reaction for 3.5 hours, the pH value of the system is monitored in real time using a pH meter to maintain the pH value at 8.5-9.5, and after the reaction is completed, the cellulose-polyethyleneimine graft copolymer is separated and dried to obtain; S4. Mix 100g of cellulose-polyethyleneimine graft copolymer, 5g of sodium citrate and 50mL of phosphate buffer evenly, then heat to 40°C, add 40wt% glyoxal at a drop rate of 0.5mL / min, keep the pH at 8.5-9.5, heat to 80°C and react for 5h, then dilute with deionized water to adjust the pH to 3-4 and the solid content to 15wt%, to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
[0038] This embodiment provides a recycling process for degradable corrugated paper, comprising the following steps: (1) Grinding the waste corrugated paper to a particle size of less than 5 mm, then adding 7 kg / T of deinking agent and water in a mass ratio of 1:3 to the waste corrugated paper, heating to 85°C, heating and stirring for 60 minutes for steaming, mixing evenly to obtain waste paper pulp, and then washing, screening, concentrating and removing impurities from the waste paper pulp to obtain paper pulp; (2) Add 0.5% of the weight of the pulp into the modified cellulose-polyethyleneimine graft copolymer reinforcing agent, mix well, heat to 100°C, and keep warm for 20 minutes; (3) Stirring a 15% silicate dispersion into the thickened pulp, wherein the amount of the silicate dispersion added is 2% of the mass of the pulp, and after mixing evenly, drying and forming the mixture, wherein the drying temperature is controlled at 110°C and the drying time is 40 minutes, to obtain a semi-finished corrugated paper product; (4) Spread the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then dry the semi-finished corrugated paper after the surface sizing, the drying temperature is controlled at 110°C, the drying time is 60 minutes, and then stand for 24 hours to obtain the finished product.
[0039] Comparative Example 1 This example is a comparative example of Example 1, except that the modified cellulose-polyethyleneimine graft copolymer reinforcing agent is replaced by acrylamide, and the other steps and parameters are the same as those of Example 1.
[0040] Comparative Example 2 This example is a comparative example of Example 1, except that sodium periodate is replaced by hydrogen peroxide. Other steps and parameters are the same as those of Example 1.
[0041] Test Example The performance of the reinforcing agents prepared in Examples 1-3 and Comparative Examples 1-2 was tested: The finished corrugated paper products prepared in the above Examples 1-3 were taken as the experimental group, and the finished corrugated paper products produced in the comparative example were selected as the control group. The tensile index, ring crush index, burst index, paper smoothness and water absorption value of the selected corrugated base paper were tested, wherein the tensile strength was measured and recorded according to GB / T12914-1991, the ring crush strength was measured and recorded according to the national standard GB / T 2679.8-1995, the burst index was detected and recorded according to the national standard GB / 6545-1998 method for determining the burst strength of corrugated paperboard, the paper smoothness was detected and recorded using a smoothness tester, and the water absorption value was detected and recorded according to the Kebo method. The test results are shown in Table 1.
[0042] Table 1. Corrugated paper performance indicators
[0043] It can be seen from the data in the table that the ring crush index, burst index and tensile index of Examples 1-3 reached 8.8-8.4, 4.8-4.5 and 47-45, respectively, which are significantly higher than the corresponding indicators of Comparative Examples 1 and 2. This shows that the modified cellulose-polyethyleneimine graft copolymer reinforcing agent can greatly improve the mechanical strength and burst resistance of paper. In addition, the paper smoothness of Examples 1-3 is 51, 48 and 45, respectively, which is significantly higher than Comparative Examples 1 and 2, showing better surface quality and printability. At the same time, the water absorption values of Examples 1-3 are 29, 31 and 32, respectively, which are lower than Comparative Examples 1 and 2, indicating that the modified cellulose-polyethyleneimine graft copolymer reinforcing agent effectively reduces the water absorption of paper and improves its water resistance.
[0044] The modified cellulose-polyethyleneimine graft copolymer reinforcing agent generated by the graft copolymerization reaction of cellulose and polyethyleneimine in this technical solution has significant performance advantages. First, the reinforcing agent has a high grafting rate and grafting density, which can significantly improve the mechanical properties of paper, including tensile strength, tear strength and burst resistance, so that it performs well when subjected to stretching and impact. Secondly, the modified cellulose-polyethyleneimine graft copolymer reinforcing agent can effectively reduce the water absorption value of paper, improve its water resistance, and maintain good stability and strength even in high humidity environments. In addition, the reinforcing agent can also significantly improve the surface smoothness and glossiness of paper, making it more suitable for high-quality printing and other surface treatments. Finally, the modified cellulose-polyethyleneimine graft copolymer reinforcing agent has excellent durability and can maintain good performance after long-term use, slowing down the rate of performance degradation and increasing the service life of paper. Even when the amount of ethyleneimine monomer is reduced, the molecular weight and viscosity of the prepolymer product decrease, and the graft copolymerization reaction rate slows down, the performance of the modified cellulose-polyethyleneimine graft copolymer reinforcing agent is still significantly better than that of the common reinforcing agent, showing its superiority in pulp processing and paper performance improvement. Compared with the acrylamide used in Comparative Example 1 and the hydrogen peroxide used in Comparative Example 2, the modified cellulose-polyethyleneimine graft copolymer reinforcing agent shows obvious advantages in mechanical properties, water resistance, surface properties and durability.
[0045] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing a modified cellulose-polyethyleneimine graft copolymer strengthening agent, characterized in that: The following steps are involved: S1. adding sodium periodate to a cellulose suspension, placing it in a dark environment for reaction, after the reaction is completed, pouring the cellulose suspension into a coagulation bath for coagulation, finally separating the coagulated cellulose from the coagulation bath, and then drying it at a temperature of 50-80° C. for 5-10 hours until it is completely dried to obtain cellulose containing aldehyde groups; S2. Add 10-16 parts of ethyleneimine monomer and 3-4.5 parts of distilled water as solvent, continue to add 0.01-0.05 parts of initiator, and prepolymerize at 55-65 ° C for 1.5-3.5h to obtain prepolymerized polyethyleneimine; S3. Add the cellulose containing aldehyde groups obtained in S1 and the prepolymerized polyethyleneimine obtained in S2 into the reaction tank, then add the initiator and the catalyst, raise the temperature to 80-90°C for graft copolymerization for 3-5h, use a pH meter to monitor the pH value of the system in real time, and keep the pH value at 8.5-9.
5. After the reaction is completed, separate and dry to obtain a cellulose-polyethyleneimine graft copolymer; S4. 80-120 parts of cellulose-polyethyleneimine graft copolymer, 4-8 parts of sodium citrate and 30-60 parts of phosphate buffer are mixed evenly, and the temperature is raised to 30-60°C. 30-40wt% glyoxal is added dropwise at a rate of 0.2-0.6mL / min, and the pH value is maintained at 8.5-9.
5. The temperature is raised to 70-80°C and the reaction is kept warm for 3-5h. Then, the pH value is adjusted to 3-4 and the solid content is adjusted to 13-15wt% by dilution with deionized water to obtain an aldehyde-modified cellulose-polyethyleneimine graft copolymer enhancer.
2. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 1, characterized in that: The preparation method of the cellulose suspension in S1 is: Adding cellulose with a mass fraction of 5-10% to an ethanol-water solution, ultrasonically treating, adding a hydrochloric acid solution with a concentration of 1-5% to react at 85-115° C., and obtaining a nanocellulose suspension after treatment; The cellulose is microcrystalline cellulose prepared by hydrolyzing waste cotton scraps with nitric acid, and the length and width of the cellulose particles are in the micron level.
3. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 2, characterized in that: The mass ratio of cellulose suspension and sodium periodate is (8-12):(10-15).
4. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 1, characterized in that: The initiators in S2 are ammonium persulfate and sodium bisulfite, wherein the mass ratio of ammonium persulfate to sodium bisulfite is (1-2):(1-3).
5. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 1, characterized in that: The catalyst in S3 is Fe 3+ and CH3CH2OH, Fe 3+ The usage ratio of CH3CH2OH is (1-3):(1-2).
6. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 5, characterized in that: The mass ratio of the cellulose containing aldehyde groups to the prepolymerized polyethyleneimine in the S3 is (6-9):(1-3).
7. The method for preparing the modified cellulose-polyethyleneimine graft copolymer strengthening agent according to claim 6, characterized in that: The method for adjusting pH in S3 and S4 is: When the pH value drops: add 0.01M NaOH solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.5; When the pH value rises: add 0.01M HCl solution dropwise, 0.1mL each time, and re-measure the pH value until it reaches 8.5-9.
5.
8. A modified cellulose-polyethyleneimine graft copolymer strengthening agent, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.
9. A recycling process for degradable corrugated paper, characterized in that: The modified cellulose-polyethyleneimine graft copolymer strengthening agent prepared by the preparation method according to any one of claims 1 to 7 comprises the following steps: (1) The waste corrugated paper is crushed, and then a deinking agent with a content of 6-9 kg / T and water with a mass ratio of 1:3 to the waste corrugated paper are added, and the mixture is stirred and heated to 80-90°C for steaming. After the mixture is evenly mixed, waste paper pulp is obtained, and then the waste paper pulp is washed, screened, concentrated, and impurities removed to obtain paper pulp; (2) Add modified cellulose-polyethyleneimine graft copolymer reinforcing agent to the pulp, mix evenly, raise the temperature to 100°C, and keep it warm for 20-30 minutes; (3) stirring a silicate dispersion having a mass fraction of 13-18% and adding it to the thickened pulp, mixing the mixture evenly and then drying and forming the mixture to obtain a corrugated paper semi-finished product; (4) Lay the semi-finished corrugated paper on a horizontal coating machine, apply the sizing agent to the surface of the semi-finished corrugated paper by the coating machine, and then irradiate the semi-finished corrugated paper with the sizing agent on the surface with an ultraviolet curing machine to obtain a finished product.
10. The recycling process of degradable corrugated paper according to claim 9, characterized in that: The silicate is one or more of sodium metasilicate, sodium silicate, potassium silicate and calcium silicate.
Citation Information
Patent Citations
Papermaking enhancer and preparation method thereof
CN105061774A
High-moisture-resistance and high-strength corrugated paper and preparation method thereof
CN107877941A
Preparation method with function of improving wet strength of paper
CN108179648A
Ecological cationic surface sizing enhancer for papermaking and preparation method thereof
CN111925453A
Multifunctional paper-based material and preparation method and application thereof
CN113262761A
Cited By
Moisture-proof flame-retardant corrugated board and preparation process thereof
CN121593368A